2006
DOI: 10.1093/hmg/ddl096
|View full text |Cite
|
Sign up to set email alerts
|

A haplotype spanning two genes, ELN and LIMK1 , decreases their transcripts and confers susceptibility to intracranial aneurysms

Abstract: The rupture of an intracranial aneurysm (IA) results in subarachnoid hemorrhage, a catastrophic neurological condition with high morbidity and mortality. Following-up on our previous genome-wide linkage study in Japanese population, we extensively analyzed a 4.6 Mb linkage region around D7S2472 on 7q11 by genotyping 168 single nucleotide polymorphisms (SNPs). SNP association and window scan haplotype-based association studies revealed a susceptibility locus for IA on a single LD block covering the 3'-untransla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Previously, we conducted a genome-wide linkage study in affected Japanese sib pairs 4 and showed through subsequent association studies that the single nucleotide polymorphisms (SNPs) of ELN and LIMK1 on chromosome 7 was significantly associated with IA. 5 We also discovered one SNP of LOXL2 on chromosome 8 associated with IA, and a possible genegene interaction of LOXL2 with ELN/LIMK1. 6 Other loci of the linkage analyses in the Japanese population include 14q23, replicated by an association study.…”
Section: Introductionmentioning
confidence: 77%
“…Previously, we conducted a genome-wide linkage study in affected Japanese sib pairs 4 and showed through subsequent association studies that the single nucleotide polymorphisms (SNPs) of ELN and LIMK1 on chromosome 7 was significantly associated with IA. 5 We also discovered one SNP of LOXL2 on chromosome 8 associated with IA, and a possible genegene interaction of LOXL2 with ELN/LIMK1. 6 Other loci of the linkage analyses in the Japanese population include 14q23, replicated by an association study.…”
Section: Introductionmentioning
confidence: 77%
“…The LIMK1 gene is located on chromosome 7q11, in which the presence of a susceptible gene for IA was indicated by linkage studies of two different ethnic groups. 22,23 Akagawa et al 24 illustrated that SNPs in ELN and LIMK1 at chromosome 7q11 might exert the synergistic effect on development of IA by affecting the stability and synthesis of vascular walls by sharing elastin signaling pathway. However, our result failed to find association with genetic variations in the ELN gene with IA, in agreement with several other studies, 25,26 suggesting that the LIMK1 gene is more likely candidate for the IA susceptibility gene at this chromosomal region.…”
Section: Discussionmentioning
confidence: 99%
“…Given a risk allele frequency of 0.2, a prevalence of 0.01 and a relative risk of 1.5, 240 cases and 240 controls are needed for an alpha of B0.05 with 80% power according to the Genetic Power Calculator (http://pngu.mgh.harvard.edu/*purcell/ gpc/), supposing that a marker allele is in complete LD with a disease allele. However, the relative risks of susceptibility genes for IA were less than 1.5 in most recent studies (Yoneyama et al 2004;Akagawa et al 2006;Inoue et al 2006;Ruigrok et al 2006aRuigrok et al , 2006bWeinsheimer et al 2007), and a marker allele is unlikely to be in complete LD with a disease allele because of the low coverage of SNP markers in theGeneChip 10 K mapping array. Thus, the power of the present study may not be sufficient to detect a relevant polymorphism for IA formation.…”
Section: Discussionmentioning
confidence: 98%
“…Linkage to 2p13 (Roos et al 2004) was shown in a large consanguineous family, but this finding has been retracted because newly diagnosed affected siblings did not show linkage to this locus (Ruigrok 2006). Among these nine linkage regions, the perlecan gene (HSPG2) at 1p36.1-36.4 (Ruigrok et al 2006a), the versican gene (CSPG2) at 5q14.3 (Ruigrok et al 2006b), elastin (ELN) and LIM domain kinase 1 (LIMK1) genes at 7q11 (Onda et al 2001;Akagawa et al 2006), collagen alpha 2(I) (COL1A2) at 7q22 (Yoneyama et al 2004), tumor necrosis factor receptor, superfamily member 13B (TNFRSF13B) at 17cen , and kallikrein at 19q13 (Weinsheimer et al 2007) have been proposed as susceptibility genes for IA. However, there has been a failure to replicate the linkage to 7q11 and the association of ELN polymorphisms with IA in several studies (Berthelemy-Okazaki et al 2005;Hofer et al 2003;Krex et al 2004;Mineharu et al 2006;Yamada et al 2003b), and linkage to 17cen also could not be replicated in a study of the same ethnic group .…”
Section: Introductionmentioning
confidence: 99%